America's Cold War : the Politics of Insecurity, Second Edition - Craig, Campbell; Logevall, Fredrik (Harvard University Press, 2020)
In a brilliant new interpretation, Campbell Craig and Fredrik Logevall reexamine the successes and failures of America's Cold War. This provocative book lays bare the emergence of a political tradition in Washington that feeds on external dangers, real or imagined, a mindset that inflames U.S. foreign policy to this day.